Therapeutic potential of natural products and antibiotics against bovine mastitis pathogen of cows and buffaloes - W Khan; SA Khan; FA Khan; S Khan; I Ullah; A Shah; I Uddin; S Khan; H Khan; MN Uddin; F Akbar; N Qayum (Veterinární Medicína, 2023)
The present study aims to evaluate the prevalence and antimicrobial sensitivity of Staphylococcus aureus associated with bovine mastitis to selected antibiotics and plant extracts. In the current study, 140 milk samples were collected from cows and buffaloes. Among the 140 samples, 93 samples were positive for sub-clinical mastitis based on the California Mastitis Test (CMT). Out of the total positive samples, 45 were confirmed for S. aureus on a Mannitol salt agar media. The antimicrobial susceptibility test revealed that 44.82% of the isolates were resistant to cefoxitin (oxacillin) confirming methicillin-resistant S. aureus (MRSA) with a higher percentage (51.61%) in the buffalo than in the cow samples. Furthermore, the PCR assay confirmed the presence of the mecA gene in all the MRSA isolates. Among the seven tested antibiotics, sulfamethoxazole + trimethoprim showed high efficacy (71.1%) against methicillin-susceptible S. aureus isolates (MSSA). Oxytetracycline and sulfamethoxazole + trimethoprim showed 20% efficacy against MRSA followed by enrofloxacin (10%). On the other hand, the tested samples from Pistacia chinensis revealed that the ethyl acetate extract of bark showed a maximum zone of inhibition of 21.3 mm against MSSA and MRSA isolates at 3 000 µg/disc. Moreover, the methanol extract of Cotoneaster microphyllus formed a 12.3 mm and 9.1 mm zone of inhibition against the MSSA and MRSA isolates, respectively.